Adsorption and binding dynamics of graphene-supported phospholipid membranes using the QCM-D technique. Issue 5 (19th January 2018) - Meléndrez, D.; Jowitt, T.; Iliut, M.; Verre, A. F.; Goodwin, S.; Vijayaraghavan, A.
Abstract : We report on the adsorption dynamics of phospholipid membranes on graphene-coated substrates using the quartz crystal microbalance with dissipation monitoring (QCM-D) technique. Abstract : We report on the adsorption dynamics of phospholipid membranes on graphene-coated substrates using the quartz crystal microbalance with dissipation monitoring (QCM-D) technique. We compare the lipid vesicle interaction and membrane formation on gold and silicon dioxide QCM crystal surfaces with their graphene oxide (GO) and reduced (r)GO coated counterparts, and report on the different lipid structures obtained. We establish graphene derivative coatings as support surfaces with tuneable hydrophobicity for the formation of controllable lipid structures. One structure of interest formed is lipid monolayer membranes which were formed on rGO, which are otherwise challenging to produce. We also demonstrate and monitor biotin–avidin binding on such a membrane, which will then serve as a platform for a wide range of biosensing applications. The QCM-D technique could be extended to both fundamental studies and applications of other covalent and non-covalent interactions in 2-dimensional materials.